Population-level decline in BMI and systolic blood pressure following mass HIV treatment: evidence from rural KwaZulu-Natal - Geldsetzer, Pascal; Bärnighausen, Till (Obesity, 2017)
Objective Clinic-based studies have shown that patients with human immunodeficiency virus (HIV) gain weight after initiation of antiretroviral therapy (ART). This study aimed to determine whether the scale-up of ART was associated with a population-level increase in body mass index (BMI) and blood pressure (BP) in a community with high HIV and obesity prevalence. Methods A household survey was conducted in rural KwaZulu-Natal before ART scale-up (in 2004) and when ART coverage had reached 25% (in 2010). Anthropometric data was linked with HIV surveillance data. Results Mean BMI decreased in women from 29.9 to 29.1 kg/m2 (P = 0.002) and in men from 24.2 to 23.0 kg/m2 (P < 0.001). Similarly, overweight and obesity prevalence declined significantly in both sexes. Mean systolic BP decreased from 123.0 to 118.2 mm Hg (P < 0.001) among women and 128.4 to 123.2 mm Hg (P < 0·001) among men. Conclusions Large-scale ART provision is likely to have caused a decline in BMI at the population level, because ART has improved the survival of those with substantial HIV-related weight loss. The ART scale-up may have created an unexpected opportunity to sustain population-level weight loss in communities with high HIV and obesity prevalence though targeted lifestyle and nutrition interventions.